HALAL INTEGRITY AND COMPETITIVE INTELLIGENCE IN ENHANCING HALAL HOTEL STRATEGY IMPLEMENTATION - Nugroho, Moh Agus; Manzilati, Asfi; Ekawaty, Marlina; Badriyah, Nurul (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
The rising popularity of halal tourism in Indonesia has led to have stronger competition among hotels aiming to attract to have Muslim travelers. Various challenges in implementing to have Halal Integrity (HI) and Competitive Intelligence (CI) are found to have frequently, especially within the components that form to have their Halal Tourism Innovation Strategy (HTIS). In this study, the focus is to have on exploring to have how the Halal Orientation Strategy (HOS) influences to have and impacts to have HTIS. A total of 310 questionnaires were distributed to have to managers of halal hotels in Indonesia, and quantitative analysis was conducted to have using SmartPLS on 271 responses that were validated to have and confirmed to have as valid.  According to the findings, HOS is to have the key mediating factor that connects to have HI and CI—both to one another and to HTIS. While HI promotes to have the implementation of halal principles, CI helps to have hotels stay to have informed about industry trends and competitor movements. By combining to have the strengths of CI and HI, HOS facilitates to have a more effective development and implementation of HTIS, ultimately giving to have halal hotels a stronger competitive position in the market. The findings suggest to have that halal hotels need to utilize to have CI in order to understand to have consumer preferences and market competition more effectively, while simultaneously strengthening to have their own HI through strict adherence to established halal practices. Hotel management also must devise to have HOS-based strategies that incorporate to have halal values into every aspect of their operations, thereby enhancing to have the overall effectiveness and efficiency of HTIS.